Halal Certification of Food and BeverageMSME’s Products in the Pacarkeling Area, Surabaya - Rakhmawati, Nur Aini; Indraswari, Rarasmaya; Ulfin, Ita; Harmami, Harmami; Rahadiantino, Lienggar; Qadariyah, Lailatul (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
This article is based on the Community Service (Kuliah Kerja Nyata / KKN) program, which was held to help solve the problems faced by MSMEs (micro, small, and medium enterprises) from the aspect of halal products certification, especially in the Pacarkeling area, Surabaya. In this program, we assist MSMEs in carrying out certification and com pleting documents so that MSMEs can apply for halal certification. Activities in this pro gram begin with assistant training, follow-up on MSMEs, training of prospective supervi sors, creating SJPH (Sistem Jaminan Produk Halal) documents, inputting data to SIHALAL, verification and validation, and finally, creating reports and documentation. In this pa per, the case study of the MSME assisted in this program is Canda, which runs in the food and beverage sector and sells ready-to-consume beverage products. The KKN team in this program intensively assists the MSMEs from the preparation stage until the announcement of halal certification. This KKN activity is documented in the form of news, digital documentation, articles, and videos of community community service. The result of this KKN activity is the Halal certification of the MSMEs in the Pacarkeling area, Surabaya